Kansas - Robinson Masters, Nancy (New York : Children's Press, 1999)
Describes the geography, plants, animals, history, economy, religions, culture, sports, arts, and people of Kansas.
Includes bibliographical referenes and index.
10 - 12 years
Keywords: Kansas -- Juvenile literature